Overcompensation carbohydrates in functional assessment in athletes sprinters - Graciana Teixeira Costa; Gislei Frota Aragao; Paulo Cesar de Almeida; Luis Sérgio Fonteles Duarte; Márcia Barros Moura Fé (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2019)
Overcompensation of carbohydrates is an efficient method to make the tissue energy reserves, making this an ergogenic effect. This effect is widely studied and proven only in long-term performance. This study aimed to investigate the influence of overcompensation of carbohydrates in the functional assessment in athletes sprinters. The sample was composed of nine sprinters at the age between 19 to 39 years, Fortaleza-CE. This research took place at a clinic specializing in sports health. Anthropometric measurements were collected and made a food history. After that, the sprinters were subjected to a normal caloric diet for six days and then carried out the effort test. After the test, the athletes remained consuming this diet for three weeks, where they started the overcompensation protocol for six days and after, subject again to the effort test. Blood samples were collected before and after the tests to check blood glucose. The results showed that although there were no significant differences in running time, effort test, cardiopulmonary fitness and blood glucose, there was a significant increase in aerobic capacity suggesting that the applied protocol can improve sports performance. We conclude that in a short-term exercise the overcompensation of carbohydrates can be an efficient ergogenic strategy.